Human movement variability in spike movement with volleyball constraint in different game positions of female elite players - Catala, J.; Fernandez-Valdes, B.; Moras, G. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: In volleyball, the volleyball spike approach movement (SM) represents one of the more sophisticated attack actions and the spike after it, is the most important ability to win a game (1). The use of nonlinear tools like entropy can be a good alternative to explore the nature of human movement and its relationship with coordinative development (2), reflecting changes in movement variability (MV) during the movement execution and overt time. SM oscillations can be evaluated through entropy calculation techniques (3) that allow to identify variability from a spatiotemporal perspective. In general, change in movement complexity with practice find that, the complexity of the attractor dynamics (pattern of expected values of the movement) could be reduced as a function of practice (4), furthermore, athletes manage to reduce the variability of their sports movements (5), in volleyball game position puntas are the player who realizes more SM in practices and competition during a season (6). The aim of this study was to identify the differences in human movement variability (MV) between game position in SM with and without ball constraint.